Attachment orientation and sexual risk behaviour among young Black gay and bisexual men. Issue 3 (2nd July 2016) - Cook, Stephanie H.; Watkins, Daphne C.; Calebs, Benjamin J.; Wilson, Patrick A.
Abstract : This mixed methods study used an explanatory sequential design to examine the relationship between attachment and sexual behaviour among young Black gay and bisexual men (YBGBM). Cross sectional online surveys and sex diaries were completed by a sample of YBGBM in New York City ( n = 153) to assess the association between adult attachment insecurity and sexual risk behaviour. The Experiences in Close Relationships Scale-Revised (ECR-R) was used to assess three types of adult attachment (i.e., secure, anxious and avoidant). Participants reported condomless sex encounters, as well as serodiscordant condomless anal sex encounters, as measures of sexual risk. Quantitative findings suggested that there were few associations between attachment type and sexual risk behaviour; only men with attachment avoidance were likely to engage in condomless sex. However, qualitative findings illuminated some of the social complexities of the association between attachment in childhood, attachment in young adulthood and intimate partnerships, which could be linked to young adult sexual risk behaviour. The study findings highlight the need for researchers to further examine the process by which individual differences in attachment orientation are related to YBGBM's sexual behaviour.